Fabrication of NaYF4:Yb3+, Tm3+-modified Ag nanocubes with upconversion luminescence and photothermal conversion properties. Issue 36 (3rd July 2019) - Chen, Ziyu; Liu, Guixia; Cui, Zhenhai; Liu, Qixin; Hong, Feng; Yu, Wensheng; Dong, Xiangting; Song, Chao
Abstract : Ag nanocubes@NaYF4 :Yb 3+, Tm 3+ multifunctional nanocomposites with florescence and photothermal ability are fabricated by a facile strategy, which enhance the mutual assistance of energy and biological application. Abstract : Herein, uniform Ag nanocube@NaYF4 :Yb 3+, Tm 3+ multifunctional nanocomposites were constructed by a facile synthetic strategy. Following the successful synthesis of Ag nanocubes, cubic phase NaYF4 :Yb 3+, Tm 3+ upconversion luminescent nanocrystals were modified on the surface of the Ag nanocubes, enhanced the mutual assistance of energy and versatility of the materials. Upon irradiation with a near-infrared laser, the nanocomposites exhibited excellent upconversion fluorescence and good photothermal conversion capability. Furthermore, the potential biological applications and biosafety of the Ag@NaYF4 :Yb 3+, Tm 3+ nanocomposites were also demonstrated; the obtained nanocomposites could achieve a good bactericidal performance and photothermal treatment of cancer cells, and they could be potentially applied in the biomedical field as a promising agent. Furthermore, this method provides a facile approach for synthesizing a multifunctional nanocomposite with different properties.